Prognostic parameters in uveal melanoma and their association with BAP1 expression. Issue 12 (21st August 2014) - van Essen, T Huibertus; van Pelt, Sake I; Versluis, Mieke; Bronkhorst, Inge HG; van Duinen, Sjoerd G; Marinkovic, Marina; Kroes, Wilma GM; Ruivenkamp, Claudia AL; Shukla, Shruti; de Klein, Annelies; Kiliç, Emine; Harbour, J William; et al.
Abstract : Aim: To determine whether BAP1 gene and protein expression associates with different prognostic parameters in uveal melanoma and whether BAP1 expression correctly identifies patients as being at risk for metastases, following enucleation of the primary tumour. Methods: Thirty cases of uveal melanoma obtained by enucleation between 1999 and 2004 were analysed for a variety of prognostic markers, including histological characteristics, chromosome aberrations obtained by fluorescence in situ hybridisation (FISH) and single nucleotide polymorphism (SNP) analysis and gene expression profiling. These parameters were compared with BAP1 gene expression and BAP1 immunostaining. Results: The presence of monosomy of chromosome 3 as identified by the different chromosome 3 tests showed significantly increased HRs (FISH on isolated nuclei cut-off 30%: HR 11.6, p=0.002; SNP analysis: HR 20.3, p=0.004) for death due to metastasis. The gene expression profile class 2, based on the 15-gene expression profile, similarly provided a significantly increased HR for a poor outcome (HR 8.5, p=0.005). Lower BAP1 gene expression and negative BAP1 immunostaining (50% of 28 tumours were immunonegative) were both associated with these markers for prognostication: FISH cut-off 30% monosomy 3 ( BAP1 gene expression: p=0.037; BAP1 immunostaining: p=0.001), SNP-monosomy 3 ( BAP1 gene expression: p=0.008; BAP1 immunostaining: p=0.002) and class 2 profile ( BAP1 gene expression: p<0.001; BAP1 immunostaining: p=0.001) and were themselves associated with an increased risk of death due to metastasis ( BAP1 gene expression dichotomised: HR 8.7, p=0.006; BAP1 immunostaining: HR 4.0, p=0.010). Conclusions: Loss of BAP1 expression associated well with all of the methods currently used for prognostication and was itself predictive of death due to metastasis in uveal melanoma after enucleation, thereby emphasising the importance of further research on the role of BAP1 in uveal melanoma.